Hidup Sehat Produktif Bebas Diabetes dengan Edukasi Kesehatan Tentang Penyakit Diabetes Melitus di Wilayah Kerja PKM Unit 1 Sumbawa - Hamid, Abdul; Hamdin Hamdin (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Diabetes Mellitus (DM) or what is commonly called diabetes is a chronic metabolic disorder caused by the insulin hormone in the body which cannot be used effectively to regulate blood sugar balance, thereby increasing the concentration of sugar levels in the blood. The aim of this community service is to increase community knowledge regarding diabetes mellitus. The benefits of community service activities are providing education about diabetes. The location of the community service activities is at BTN Bukit Permai in the Kerka Community Health Center Unit 1 Sumbawa area. This community service activity has been carried out well involving public health students and nursing students, in carrying out outreach activities to the community with the title